2014
DOI: 10.1111/sms.12362
|View full text |Cite
|
Sign up to set email alerts
|

Young athletes' awareness and monitoring of anti‐doping in daily life: Does motivation matter?

Abstract: This study was a preliminarily investigation into the prevention of unintentional doping on the basis of self-determination theory (SDT). Specifically, we examined the relationship between athletes' motives for doping avoidance and their behavior when offered an unfamiliar food product. Participants were young Australian athletes (n = 410) that were offered a free lollipop prior to completing a questionnaire. It was noted whether participants refused to take or eat the lollipop and whether they read the ingred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 52 publications
(103 reference statements)
1
27
0
Order By: Relevance
“…We and others have reported that the awareness of, and intention or adherence to avoiding unintentional doping is related to a number of psychological variables such as motivation, social-cognitive variables and beliefs, and self-control 2 6 8 9. Extending this research would help sport governing bodies, antidoping agencies and sport professionals, to establish essential training and social environmental conditions that empower athletes to self-monitor and act appropriately to help prevent unintentional doping.…”
Section: How To Help Responsible Athletes Prevent Unintentional Doping?mentioning
confidence: 78%
See 1 more Smart Citation
“…We and others have reported that the awareness of, and intention or adherence to avoiding unintentional doping is related to a number of psychological variables such as motivation, social-cognitive variables and beliefs, and self-control 2 6 8 9. Extending this research would help sport governing bodies, antidoping agencies and sport professionals, to establish essential training and social environmental conditions that empower athletes to self-monitor and act appropriately to help prevent unintentional doping.…”
Section: How To Help Responsible Athletes Prevent Unintentional Doping?mentioning
confidence: 78%
“…However athletes may dope unintentionally because they are not aware that food, drinks, supplements, or medications may contain doping substances 2 3. Therefore, one of the key antidoping strategies of WADA, apart from doping control, is to enhance athletes’ antidoping awareness and their capacity to avoid unintentional doping.…”
mentioning
confidence: 99%
“…Moreover, other confounding effects such as participants' prior experience, knowledge, and belief of antidoping were likely to elevate the error variances of the study. Using lollipops as a behavioral means to evaluate preventive action toward unintended doping (Chan, Donovan, et al, 2014) might also be vulnerable to the influences of socially desirable responses and individual discrepan cies in food preference. Future studies may adopt more objective psychological measures (e.g., performance on self-regulatory tasks, implicit association test for implicit doping attitudes) and randomized factorial experiments to test the role of self-control on doping intention, aware ness, and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…This study used a dataset reported in previous studies Chan, Donovan, et al, 2014; based on a convenience sample of athletes that were used to test different hypotheses.…”
Section: Notesmentioning
confidence: 99%
See 1 more Smart Citation